Lung function tests in children with SCD - P, JOSHI M.; R, BORKAR (International Journal of Psychosocial Rehabilitation, 2020)
Background: Hemoglobin S(HbS)occurs due to one base pair change which encodes valine instead of glutamine in the 6th position in the beta-globin molecule. HbS cells change from a normal biconcave disc to a sickled form with resultant decreased deformability in deoxygenated conditions, which leads to occlusion of microvasculature followed with infarction, dysfunction and pain. The sickling phenomenon is exacerbated by hypoxia, acidosis, increased or decreased temperature and dehydration. Pulmonary function tests help in analysing the status in both physiological and pathological conditions.Objectives: To study the incidence of lung abnormality in sickle cell children & the type of lung disease- obstructive or restrictive. Methodology: The study is being conducted bedside with the help of MIR spirometer at AVBRH hospital, Sawangi on children with SS/AS pattern sickle cell disease/anemia from age 4-16 years.Results: the results would be undertaken with SPSS. Conclusion- will be based on the findings of our study.